2013
DOI: 10.1007/s10658-013-0195-6
|View full text |Cite
|
Sign up to set email alerts
|

A review on crop losses, epidemiology and disease management of rice brown spot to identify research priorities and knowledge gaps

Abstract: Rice brown spot (BS) is a chronic disease that affects millions of hectares of rice every growing season, grown by some of the most resource-poor farmers. Despite its widespread occurrence and impact, much still needs to be understood about BS. Reported yield losses in relative terms vary widely from 4 to 52 %. However, accurate, systematic estimates are lacking. BS is conventionally perceived as a secondary problem that reflects rice crops that experience physiological stresses, e.g. drought and poor soil fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
80
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 53 publications
(68 reference statements)
0
80
0
2
Order By: Relevance
“…It is a major constraint limiting the optimal production of crops included rice. Many studies have reported yield loss due to rice diseases in different intensity, from light to very severe yield losses (Sparks et al, 2012;Barnwal et al, 2013;Kihoro et al, 2013). As an example, the estimated annual loss of rice only due to blast disease was enough to feed 60 million people for one year (Pennisi, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is a major constraint limiting the optimal production of crops included rice. Many studies have reported yield loss due to rice diseases in different intensity, from light to very severe yield losses (Sparks et al, 2012;Barnwal et al, 2013;Kihoro et al, 2013). As an example, the estimated annual loss of rice only due to blast disease was enough to feed 60 million people for one year (Pennisi, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Bipolaris oryzae and Fusarium moniliforme, responsible for the brown spot disease and the bakanae disease in rice, respectively, are mainly found in rice seeds (Mew and Gonzales, 2002). Losses due to these pathogens range from 4 to 52% for B. oryzae (Barnwal et al, 2013) and 4 to 20% for F. moniliforme (Reddy and Sathyanarayana, 2001). Seed dressing of rice to overcome these pathogens has many advantages, including the protection of seed and seedlings against pathogens in the early stages of germination and development.…”
Section: Introductionmentioning
confidence: 99%
“…The disease is of great importance in several countries and has been reported to cause enormous loss in grain yield (upto90%) particularly when leaf spotting phase assumes epiphytotic proportions as observed in Great Bengal Famine during 1942(Ghoseet al, 1960. The disease especially occurs in environment where water supply is scarce combined with nutritional imbalance particularly lack of nitrogen (Baranwal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%